2017
DOI: 10.1039/c7ra03328a
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational study of the inclusion complexes of β-cyclodextrin with the chemical warfare agent soman (GD) and commonly used simulants

Abstract: The inclusion complexation of the Chemical Warfare Agent soman (GD) by β-cyclodextrin is studied by both experimental and computational approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
(38 reference statements)
1
14
1
Order By: Relevance
“…In agreement with the literature, this appears to be driven by the hydrophobic inclusion of aliphatic groups [ 16 , 37 ]. In contrast to reports by ourselves and others on the inclusion of OP CWAs and related compounds with cyclodextrins [ 13 , 23 ], the affinity of the complexes is in most cases fairly weak. This may be a result of non-optimized size match between the aliphatic side-chains of the guest species and the internal hydrophobic cavity, or the relative hydrophobic nature of the cyclodextrin and SCX cavities.…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…In agreement with the literature, this appears to be driven by the hydrophobic inclusion of aliphatic groups [ 16 , 37 ]. In contrast to reports by ourselves and others on the inclusion of OP CWAs and related compounds with cyclodextrins [ 13 , 23 ], the affinity of the complexes is in most cases fairly weak. This may be a result of non-optimized size match between the aliphatic side-chains of the guest species and the internal hydrophobic cavity, or the relative hydrophobic nature of the cyclodextrin and SCX cavities.…”
Section: Resultscontrasting
confidence: 95%
“…Quantitative 1 H-NMR titration experiments were again conducted and association constants determined by EQNMR analysis as K 11 = 75 and <10 M −1 for the SCX4 and SCX6 hosts, respectively. It should be noted that, unlike with β-cyclodextrin [ 23 ], there was no observation of chiral discrimination as a result of complex formation. This is expected, given that the SCX hosts are achiral and chiral recognition using calixarenes is usually achieved through either the incorporation of chiral functionality or of asymmetry [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore vital to consider the appropriate properties of any simulant chosen to aid in the development of novel OP CWA detection, decontamination, or remediation methodologies. [21][22][23][24] Recently, work undertaken by Snurr and Mendonca, has shown that density functional theory (DFT) can be used to study the mechanism of OP hydrolysis, which has resulted in the development of a quantitative structure activity relationship (QSAR) model that enables the identification of appropriate OP CWA simulants for decontamination purposes. 25 However, when considering supramolecular technologies, the moiety target is often selective coordination of the polar PvO functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 11-15 are commercially available species commonly used to simulate OP CWAs. The structures of simulants 5-10 and 16-26 were designed to fulfil the following criteria: charge neutrality; not readily ionised under experimental conditions; containing a single electrophilic site (S or P); and containing a single HBA centre (either a PvO (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), or OvSvO (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)).…”
Section: Introductionmentioning
confidence: 99%